Spud - Van de Ruit, John. (London : Penguin Books, 2008)
Spud Milton is embarking on his first year at an elite boys-only private school. Cursed with parents well beyong the lunatic fringe and a dormitory full of strange characters (Gecko, Rambo and Mad Dog to name just a few), Spud discovers that the firs steps along the path to manhood aren't the easiest ones to take.There will be trouble ahead, from illegal night swimming to ghostbusting to teacher baiting. Armed only with his wits and his diary, Spud invites us into the mind of a boy whose eyes are being opened to girls, friendship and complete insanity.
Keywords: Milton, Spud (Fictitious character -- Fiction; Boarding schools -- South Africa -- Fiction; Private schools -- South Africa -- Fiction; Teenage boys -- South Africa -- Fiction; Teenage boys -- South Africa -- Fiction; Single-sex schools -- Fiction; Diary fiction